The Genesis of Cerebellar GABAergic Neurons: Fate Potential and Specification Mechanisms - Leto, Ketty; Rolando, Chiara; Rossi, Ferdinando (Frontiers in Neuroanatomy, 2012)
The variety of neuronal phenotypes that populate the cerebellum derives from progenitors that proliferate in two germinal neuroepithelia: the ventricular zone generates GABAergic neurons, whereas the rhombic lip is the origin of glutamatergic types. Progenitors of the ventricular zone produce GABAergic projection neurons (Purkinje cells and nucleo-olivary neurons) at the onset of cerebellar neurogenesis. Later on, however, these progenitors migrate into the prospective white matter, where they continue to divide up to postnatal development and generate different categories of inhibitory interneurons, according to precise spatio-temporal schedules. Projection neurons derive from discrete progenitor pools located in distinct microdomains of the ventricular zone, whereas interneurons originate from a single population of precursors, distinguished by the expression of the transcription factor Pax-2. Heterotopic/heterochronic transplantation experiments indicate that interneuron progenitors maintain full developmental potentialities up to the end of cerebellar development and acquire mature phenotypes under the influence of environmental cues present in the prospective white matter. Furthermore, the final fate choice occurs in postmitotic cells, rather than dividing progenitors. Extracerebellar cells grafted to the postnatal cerebellum are not responsive to local neurogenic cues and fail to adopt clear cerebellar identities. On the other hand, cerebellar cells grafted to extracerebellar regions retain typical phenotypes of cerebellar GABAergic interneurons, but acquire specific traits under the influence of local cues. These findings indicate that interneuron progenitors are multipotent and sensitive to spatio-temporally patterned environmental signals that regulate the genesis of different categories of interneurons, in precise quantities and at defined times and places.